The Effect Of Population And Economic Growth Towards Poverty Level In The East Borneo Province - Abdul Hakim; Sutrisni Sutrisni (Jurnal Penelitian IPTEKS, 2020)
The purpose of this research was to determine the effects of population growth and economic growth on poverty levels in East Borneo Province.  The analytical tool used in this research multiple linear regression with the help of the Eviews 10 program. Based on the results of the regression analysis, indicated that partially population growth shows the value of t-count was 0.413709 with the value of t-table was 2.77645, then t-count t-table so that population growth was positive and has no significant effect on poverty levels in East Borneo Province in 2011 to 2017, and economic growth showed that the value of t-count was 3.521670 with t-table 2.77645, then t-count t-table so that economic growth was positive and has a significant effect on poverty levels in East Borneo Province from 2011 to 2017.  While simultaneously the results indicated that population growth and together economic growth shows the value of F-count was 8.39 and F-table was 6.94, the value of F-count F-table so that population growth and economic growth together have a significant effect on poverty levels in East Borneo Province in 2011 to 2017 at a 95% confidence level.